Degradation of Plant Fiber Reinforced Polymer Composites - Wahyu Purwo Raharjo; Dody Ariawan; Kuncoro Diharjo; Wijang Wisnu Raharjo; Bambang Kusharjanta (Advanced Aspects of Engineering Research Vol. 5, 2021)
This chapter review the influence of moisture, thermal, fire and ultraviolet radiation on the characteristics of plant fiber-polymer composites. The effect of chemical treatments and additives such as fiber treatments, fire retardants and stabilizers toward UV radiation are also discussed. Based on the analysis, the strength of a plant fiber-polymer composite is obtained by optimum fiber content, but the presence of fiber enables the deterioration of the composite due to the moisture. The improvement of fiber-matrix interface by fiber treatments enhance the composite resistance to moisture but the fibers become less resistant when subjected to weather. The fire retardant and UV stabilizers improve fire and outdoor performance of plant fiber-polymer composites. However, their mechanical characteristics tend to decrease. It is concluded that to attain a balance between mechanical characteristics and weather resistance, the optimum blend ratio of chemical additive should be determined.